Audit fees: an analysis of the family and nonfamily business listed on the BM&FBovespa - Beck, Franciele; Cunha, Paulo Roberto da; Franz, Leandro (Review of Business Management, 2015)
Objective – Examine the relationship between audit fees and the quality of financial information in familiar and non-familiar companies listed on the BM&FBovespa. Design/methodology/approach – Descriptive, documentary research with application of average test and linear regression model, using data from 2009, 2010 and 2011 of a sample of 133 family businesses and 128 non-familiar BM&FBovespa. The basis for the study was Ghosh and Tang (2015). Findings - The findings indicate a rejection of the hypothesis through the average test and regression model, in which the variable dependent (family firms) was not statistically significant. This result differs from that obtained by Ghosh and Tang (2015) and makes inference to the characteristics of the companies and the Brazilian market. Practical implications – Enabled the discussion on the relationship between audit fees and the structure of ownership and control of Brazilian companies, going through the theme of quality of financial information. It also helped the identification of key explanatory variables for audit fees. In family firms included: size, foreign-sales, mergers and/or acquisitions (M&A), Big Four, and in non-family firms: size, regulation, busy-season, Big Four and auditor-tenure.